Perceived organizational support and impact on high performance Analytical research in the colleges of the University of Baghdad - Amer, Abeer DheifAllah; AL-joufi, Alya Saeed (Journal of Economics and Administrative Sciences, 2021)
The research tagged (Perceived Organizational Support in High Performance) deals with identifying the extent of the impact of perceived organizational support as an explanatory variable on high performance as a response variable for the purpose of reaching appropriate mechanisms that enable colleges of the University of Baghdad to exploit the perceived organizational support in achieving the required high performance and pursuit of its goals. The researcher relied on the descriptive and analytical approach in carrying out the research. An intentional sample was selected and reached (70) persons from the higher leadership of the colleges represented by (deans, assistants deans, heads of departments) that represented the entire study population, The research included (8) colleges of the University of Baghdad, and the questionnaire was used as a basic tool in data collection. Therefore, the questionnaire included (35) items distributed on two axes and was subjected to statistical analysis using the (SPSS V.25 program; Excel V.16), It was prepared based on a number of measures using (Likert), The answers were also strengthened by observations and personal interviews that the researcher conducted with some of the research samples, In addition to a set of statistical methods such as (arithmetic mean, standard deviation, relative importance, coefficient of determination (R2), coefficient of variation, rank correlation coefficient (Pearson), (F) test, simple linear regression analysis). The research reached bundles of conclusions, the most important of which can be considered perceived organizational support and high performance as two sides of the same coin, given that high performance is the result of organizational support and perceived in its dimensions is influential and its presence will contribute to generating high performance distinguished, and based on the conclusions reached, a group of The recommendations were the most important of which was that the management of the researched colleges should choose the appropriate competencies with scientific activity and be strong and integrated teams in all respects and thus be proud of their achievements that they present from distinguished work